Dukungan Sosial Keluarga Penyandang Disabilitas dalam Keterbukaan Akses Menempuh Pendidikan - Fitria Dayanti; Farid Pribadi (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
People with disabilities have equal rights in life, one of which is to take education. As a group that is vulnerable to injustice, family support as the closest person has an important role in the survival of people with disabilities. The government, community, and family should provide support and opportunities for people with disabilities to go to school in order to create independence for them. But in reality, there are still many people with disabilities who do not get access and support for education. Therefore, this study aims to explore forms of social support for families with disabilities in open access to education, by conducting case studies on families of people with physical disabilities. The method used in this research is descriptive qualitative. The results of the study found that there were five forms of family social support, especially parents for people with physical disabilities in Labang District in health education, namely support in instrumental aspects, informational aspects, emotional aspects, aspects of support for self-esteem, and network aspects.